Online quiz for STEM assumed knowledge self-assessment by first year science students: a pilot study. Issue 5 (28th May 2023) - Johnston, Peter R.; Watters, Dianne J.; Brown, Christopher L.; Williams, Michael L.; Loughlin, Wendy A.
ABSTRACT: This study aimed to adapt the Get Set2 quiz and design a diagnostic quiz for implementation under assumed knowledge admissions into university science degrees. The GetReady Quiz that was designed, comprised five modules benchmarked against the high school curriculum in Mathematics, Chemistry and Biology. The significance of this study stems from the development of an alternate approach to support students, with deficiencies in mathematical skills, who enter university STEM programmes with recommended foundational knowledge in mathematics and science. A mixed-mode research methodology was employed in which quiz design was coupled with implementation and evaluation with a pilot study. The GetReady Quiz design featured five discipline modules in Mathematics, Chemistry and Biology, with progression of question difficulty. Knowledge gaps and apparent difficulties for some students with conceptual understanding were evident. Students displayed a realization of their lack of knowledge by reporting that completion of the GetReady Quiz helped them identify areas for revision. The findings indicated that the GetReady quiz was appropriate for assumed knowledge self-diagnosis for commencing students. Approaches to diagnostic testing, such as the GetReady Quiz, should be recommended, if not compulsory, for university students who commence study with STEM assumed knowledge admission.